On the formation of membership functions for fuzzy sets in the logical representation of knowledge - Serov, Vladimir V (IOP conference series. Materials Science and Engineering, 2020)
The problems of using characteristic membership functions to describe fuzzy knowledge in the form of a logical calculus of fuzzy first-order predicates are considered. Some possible types of functions and methods for their preparation are described. The possibility of using these methods for the development of expert and intelligent systems in various subject areas, such as enterprise management, recognition of the structures of polyatomic molecules, is shown.